Carbon removal of mold sample by femtosecond laser - Abu Bakar, Mohamad Aizat (2018)
Clean mold tool is important in large scale production of high quality integrated circuit chip. Conventional mold tool cleaning techniques often involve chemicals as cleaning agent which is costly and polluting process hence light is suggested as a non-chemical agent alternative. High intensity light energy released in very short pulse duration can remove the contaminant particles from mold tool surface. Femtosecond laser of 1025 nm wavelength and pulse duration of 400 fs is utilized to remove carbon particle on chromium nitride surface. The effectiveness of carbon removal is determined by the comparison of surface imaging, elemental composition distribution and the surface roughness value of the mold tool surface condition before and after laser ablation at different powers and distances. The obtained result shows great carbon content removal of 75% and lowest induced damage percentage of 10% at laser power 1.7 W and ablation distance of 29.0 mm while highly preserving structure of the mold tool surface roughness value of 0.273 nm. Effective and precise carbon removal is achieved by using the optimum laser power and ablation distance onto target surface for laser cleaning on mold tool. The main advantage of this method is chemical free process and leading to a green technological innovation in mold tool cleaning industries.